Undescribed Phyllocladane-Type Diterpenoids from Callicarpa giraldii Hesse ex Rehd. and Their Anti-Neuroinflammatory Activity - Xu Liang; Qi Gong; Yuting Xu; Jiaxing Mu; Chunping Tang; Bintao Hu; Changqiang Ke; Sheng Yao; Haiyan Zhang; Yang Ye (Molecules)
Callicarpa giraldii Hesse ex Rehd. is an endemic plant in China and has long been used as a traditional medicine in several provinces. Although the plant has been reported to contain flavonoids, triterpenes, and alkaloids, this study represents the first report of the isolation of phyllocladane-type diterpenoids, a relatively rare class of compounds. In this study, 18 new phyllocladane-type diterpenoids (7–24) were isolated and structurally elucidated, including eight uncommon 3,4-seco phyllocladane-type diterpenoids (15–22) and two unusual phyllocladane-type diterpene dimers (23–24), along with six known analogues (1–6). Their structures were elucidated by a comprehensive analysis of 1D and 2D NMR, IR, and HRESIMS data. The absolute configurations were determined by single crystal X-ray diffraction experiments, DFT NMR calculations, and TDDFT ECD calculations. Based on the obtained and reported spectroscopic data, we refined a rule to distinguish phyllocladane-type diterpenoids from their diastereomeric ent-kaurane-type compounds. Additionally, the isolated compounds were evaluated for their in vitro anti-neuroinflammatory activity against lipopolysaccharide (LPS)-induced inflammation in BV-2 microglial cells. Compounds 5, 10, 13, 18, 19, and 20 showed moderate inhibitory activity at the concentration of 20 μM, with compounds 5 and 13 markedly reducing the mRNA levels of the pro-inflammatory cytokines IL-1β, IL-6, and TNF-α at this concentration.